PENERAPAN MODEL PEMBELAJARAN TANDUR UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDK TUALARAN KABUPATEN MALAKA - Ummu Aiman; Julhidayat Muhsam; Aryanti (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2023)
This research aims to improve the learning outcomes of Theme 8 class IV SDK Tualaran Malaka students by applying the Tandur learning model. The type of research used in this research is Classroom Action Research (CAR). The subjects of this study were fourth grade students at SDK Tualaran, Malaka Regency, with a total of 17 students. Data collection techniques carried out in this study were observation and learning achievement tests. The results of the first cycle of research obtained an average score of 66.76, with a completeness percentage of 47%, the results of observations of student activities were 70.46 (enough) and the results of observations of teacher activities were 78.57 (enough). After the second cycle was carried out, the average score was 81.17 with a completeness percentage of 88%, the results of observations of student activities were 87.99 (Good) and the results of observations of teacher activities were 98.21 (Good). So that the application of the Tandur learning model to science learning can improve the learning outcomes of students in class IV SDK Tualaran, Malacca Regency.